Esensi Ritual Melukat sebagai Daya Tarik Wisata Spiritual - Nyoman Mahardika; Angga Angkasa (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2018)
In the midst of the rapid interest of the Hindu community in Bali to perform the melukat ritual, an interesting phenomenon occurred in the Penglukatan Village of Pekraman Sebatu Village in Tegallalang Gianyar, Bali, where everyone can see for themselves the changes in water that occur as a sign of a real cleaning process. This 'peculiarity' resulted in word of mouth propaganda phenomenon, making this place of knowledge suddenly famous. Not only the local community, foreign guests are also attracted by the power of mouth froma phenomenon that was first discovered accidentally by a foreign tourist. Thousands of foreign tourists join in every month. This study intends to provide different perspectives that understand and carry out melukat essence, related to self-empowerment efforts to improve the quality of people's lives, because basically every ritual is only a tool for self-empowerment, not purpose. Also reviewing this phenomenon from a tourism perspective, given the positive response from the 'market'. The novelty that is to be offered is aform of spiritual tourism that does not sell sensations, but tours that promote self-empowerment as a result of the declaration of local wisdom that is able to provide an inner experience that is recharge their spiritual spirituality. As well as being able to be communicated logically, scientifically and interestingly.